2018
DOI: 10.2334/josnusd.17-0223
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the periodontal status and prevalence of red complex periodontal pathogens in a Japanese population

Abstract: This large-scale study cross-sectionally examined the periodontal status and prevalence of "red complex" bacteria (Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia) in Japanese adults. A total of 977 participants were enrolled in the study. Probing depth (PD), bleeding on probing (BOP), and bone crest level (BCL) were recorded, and the presence of red complex bacteria in the saliva was examined using polymerase chain reaction. The mean BCL value and the percentage of sites with a PD ≥4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…In the present study, P. gingivalis infection was more common among elderly (≥65 years old) subjects. Previously, the P. gingivalis detection rate was observed to significantly increase with age, while that of T. denticola and T. forsythia was comparably high across all age groups (25). In the current study, participants with ≥4-mm pockets exhibited higher positive rates of the red complex bacteria P. gingivalis and T. denticola compared with those with <4-mm pockets.…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, P. gingivalis infection was more common among elderly (≥65 years old) subjects. Previously, the P. gingivalis detection rate was observed to significantly increase with age, while that of T. denticola and T. forsythia was comparably high across all age groups (25). In the current study, participants with ≥4-mm pockets exhibited higher positive rates of the red complex bacteria P. gingivalis and T. denticola compared with those with <4-mm pockets.…”
Section: Discussionsupporting
confidence: 50%
“…Nevertheless, the presence of P. gingivalis has been positively correlated with greater probing depth and periodontitis severity. 17,32,33 Likewise, in our study, Group C was associated with greater mean probing depth and the proportion of sampled sites with PD and CAL ≥8 mm was greater in P. gingivalis-positive than P. gingivalis-negative patients.…”
Section: Discussionsupporting
confidence: 71%
“…Accordingly, a number of cross-sectional PCR-based studies have compared salivary levels of putative periopathogens, especially Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, Prevotella intermedia and Aggregatibacter actinomycemtomitans in saliva from patients with periodontitis to those of orally healthy controls. A recent study from 2019 reported salivary levels of the JP2 clone of A. actinomycemtomitans to associate with clinical attachment loss in Moroccan adolescents [34], whereas a large-scale study comprising 977 Japanese individuals showed salivary levels of P. gingivalis to correlate with percentage of sites with probing pocket depth ≥4 mm [35]. In addition, a cross-sectional study of a Finnish population (n = 462) documented that combined salivary levels of P. gingivalis, P. intermedia and T. forsythia were associated with periodontitis [36].…”
Section: Periodontitismentioning
confidence: 98%